ANALISIS PENGARUH LAJU AKRESI DAN KOEFISIEN KONVEKSI PADA EVOLUSI BINTANG DI PRA DERET UTAMA: STUDI KASUS BINTANG TIPE T TAURI - Indriani, Putri
Three phases make up the star's evolution stage: pre-main sequence, main sequence, and post-main sequence. For the pre-main sequence phase, various parameters can affect the evolution, including the convection coefficient and the accretion rate. Convection becomes the dominant energy transport in the pre-main sequence, particularly as the star moves down the Hayashi trail. The coefficient of convection becomes an efficiency parameter for convection. In the HR diagram, the stars with higher coefficients are more to the left, which means they have higher temperatures. Furthermore, the accretion in the young star increases the star's mass during the star formation process, which affects the star's inner structure due to mass addition. The radiated luminosity and the star's radius decrease with increasing accretion rate, and the increasing accretion rate also affects the star's age in the pre-main sequence. In this study, we use data from T Tauri-type stars, an example of young, low-mass stars. We model them for obtaining a pre-main sequence evolutionary track on the HR diagram and the most suitable coefficient of convection value with the star data used. This study's purpose is to study and analyze the influence of accretion rate and coefficient of convection on the evolution of low-mass stars in pre-main sequence T Tauri type star data using the star evolution code MESA r12115. By using the known parameters T Tauri type star, we can compare the value of the convection coefficient that is more suitable for the T Tauri type star and how the parameters change during the pre-main sequence until they reach ZAMS.